Images of miraculous healing in the early modern Netherlands - Kaminska, Barbara A. (Brill's studies on art, art history, and intellectual history, 2021)
"Images of Miraculous Healing in the Early Modern Netherlands explores the ways in which paintings and prints of biblical miracles shaped viewers' approaches to physical and sensory impairments and bolstered their belief in supernatural healing and charitable behavior. Drawing upon a vast range of sources, Kaminska demonstrates that visual imagery held a central place in premodern disability discourses, and that the exegesis of New Testament miracle stories determined key attitudes toward the sick and the poor. Addressed to middle-class collectors, many of the images analyzed in this study have hitherto been neglected by art historians"--